PERKEMBANGAN INDUSTRI KERAJINAN BATOK KELAPA DI GAMPONG UJONG KAREUNG, KECAMATAN SUKAJAYA, SABANG, 2005-2017 - Ika Nadia Lestari; Teuku Abdullah; Anwar Yoesoef (Universitas Syiah Kuala, 2017)
ABTRASCTCoconut Shell Industry includes small industries. The industry is growing in Gampong Ujong Kareung, Kecamatan Sukajaya, Sabang. The existence of this industry has impacted the lives of local people, especially in social, economic and cultural aspects. The research entitled